Types of figurative language in Christina Perri’s songs - Netta, Ayuna (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2023)
This study examined the types of figurative language found in Christina Perri’s songs. This descriptive study used a qualitative approach. Data were taken from the lyrics of Christina Perri’s songs. Content analysis was used to examine the data in this study. The results of this study revealed that there were several kinds of figurative language in Christina Perri’s songs. They were metaphor, simile, personification, symbolism, alliteration, assonance, consonance, hyperbole, oxymoron, and imagery. The study on figurative languages in songs provides important educational implications such as promoting language proficiency, encouraging literary analysis and critical thinking, raising understanding of cultures, stimulating the creative process, and building emotional intelligence for students and teachers during teaching and learning process.